View of the Bhandasar Jain Temple - Temples of India Project Team (Jio Institute, 2024)
View of the Bhandasar Jain Temple as seen from the northeast corner of the complex. Built in the shekhari style of temple, the temple has an imposing shekhari shikhara (multi-spired superstructure). The plan of the temple consists of a garbhagriha (sanctum sanctorum), mandapa (pillared hall) and a mukhamandapa (front porch). Domes roof the mandapa and shekhari shikhara is atop the garbhagriha.